1999
DOI: 10.1111/j.1744-6570.1999.tb00165.x
|View full text |Cite
|
Sign up to set email alerts
|

An International Look at Selection Practices: Nation and Culture as Explanations for Variability in Practice

Abstract: A survey of 959 organizations in 20 countries was undertaken to assess whether differences in staffing practices are due in part to nation and culture. Cultural differences in uncertainty avoidance and, to a lesser extent, power distance, explained some of the national differences observed in the extensiveness of method use. Implications for understanding the best approaches to selection on a global basis are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
254
0
7

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(271 citation statements)
references
References 18 publications
10
254
0
7
Order By: Relevance
“…MAS was positively related to individual bonuses and commissions, career breaks, and maternity leave, and negatively related to flexible benefits and workplace childcare. From survey data of almost 1,000 companies in 20 countries, Ryan et al (1999) found that, as UA increased, the number used and extent of verification methods in selection processes decreased (opposite to what was expected). The number of test types, extent of testing, number of interviews, use of a fixed list of interviews, and number of methods of auditing their selection processes all increased as UA increased.…”
Section: Research Challengesmentioning
confidence: 78%
See 1 more Smart Citation
“…MAS was positively related to individual bonuses and commissions, career breaks, and maternity leave, and negatively related to flexible benefits and workplace childcare. From survey data of almost 1,000 companies in 20 countries, Ryan et al (1999) found that, as UA increased, the number used and extent of verification methods in selection processes decreased (opposite to what was expected). The number of test types, extent of testing, number of interviews, use of a fixed list of interviews, and number of methods of auditing their selection processes all increased as UA increased.…”
Section: Research Challengesmentioning
confidence: 78%
“…main , Cable and Judge (1994) main , Ramamoorthy and Carroll (1998) main , Earley (1986) main , main Newman and Nollen (1996) main , Roth and O'Donnell (1996) main , Schuler and Rogovsky (1998) main , Ryan et al (1999) main Leadership Casimir and Keats (1996) main , Pillai and Meindl (1998) …”
mentioning
confidence: 99%
“…Generally, we believe that recruitment and selection practices are fairly similar in Belgium and the United States. For example, a comparative study of international selection practices did not reveal marked differences between the United States and Belgium (Ryan, McFarland, Baron, & Page, 1999). In addition, many multinationals and HR service providers have divisions in both the United States and Belgium.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting conclusion was that the size of the organizations surveyed had a much less significant impact on the use of different selection procedures than the country of the organization. A recent study (Ryan, McFarland, Baron, & Page (1999) surveyed 959 organizations in 20 countries and confirmed that national differences accounted for considerable variance in selection practices.…”
Section: Use Of Selection Procedures Across Countriesmentioning
confidence: 91%
“…Although the potentially influencing contextual factors are abounding, empirical research to test the impact of these factors has been limited. To our knowledge, only one stud y (Ryan et al, 1999) linked cultural differences to the variability in selection procedure use. Ryan et al (1999) Ryan et al hypothesized that organizations in cultures high in power distance would be the ones where selection decision making is more hierarchical and were peers are less likely to be interviewers.…”
Section: Explanations For Variability In Use Of Selection Procedures mentioning
confidence: 99%